Nearlattices Whose Sets of Principal n-ideals Form Relatively Normal Nearlattices - Raihan, M. S.; Noor, A. S. A. (Journal of Scientific Research, 2010)
We generalize several results of relatively normal nearlattices in terms of n-ideals. We introduce the notion of relative n-annihilators in a nearlattice and include some interesting results on this. Several characterizations of the set of principal n-ideals Pn(S) are given which forms a relatively normal nearlattice in terms of relative n-annihilators. It is shown that Pn(S) is relatively normal if and only if for any two incomparable prime n-ideals P and Q, P Ú Q=L. Keywords: Relatively normal nearlattice; Relative n-annihilator; Incomparable prime n-ideals. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i1.3955 J. Sci. Res. 3 (1), 35-42 (2011)